2010
DOI: 10.1016/j.neuron.2010.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The Apical Complex Couples Cell Fate and Cell Survival to Cerebral Cortical Development

Abstract: Cortical development depends upon tightly controlled cell fate and cell survival decisions that generate a functional neuronal population, but the coordination of these two processes is poorly understood. Here we show that conditional removal of a key apical complex protein, Pals1, causes premature withdrawal from the cell cycle, inducing excessive generation of early-born postmitotic neurons followed by surprisingly massive and rapid cell death, leading to the abrogation of virtually the entire cortical struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
116
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 76 publications
(97 reference statements)
15
116
3
6
Order By: Relevance
“…Apical polarity proteins are fundamentally important for neural development, that is, Par3 and Par6 localize apically and promote proliferation of neural progenitors in the developing mouse cerebral cortex [16], overexpression and mislocalization of aPKCf increases neural progenitor numbers [15], and very recently it has been shown that loss of Pals1, notably a member of the Crumbs complex, resulted in massive cell death during cortical development [19]. This is similar to our Crb2-KD phenotype.…”
Section: Crb2 Is Required For Stabilization Of Apical Polarity Proteinssupporting
confidence: 84%
See 1 more Smart Citation
“…Apical polarity proteins are fundamentally important for neural development, that is, Par3 and Par6 localize apically and promote proliferation of neural progenitors in the developing mouse cerebral cortex [16], overexpression and mislocalization of aPKCf increases neural progenitor numbers [15], and very recently it has been shown that loss of Pals1, notably a member of the Crumbs complex, resulted in massive cell death during cortical development [19]. This is similar to our Crb2-KD phenotype.…”
Section: Crb2 Is Required For Stabilization Of Apical Polarity Proteinssupporting
confidence: 84%
“…GSK-3b is a core component of Wnt/b-catenin signaling [10] and a key regulator of neurogenesis [11][12][13]. Although several components of the Par complex have been reported to play a pivotal role in neurogenesis [14][15][16][17][18], and a recent study shows that Pals1 is important for cell survival in the cerebral cortex [19], almost nothing is known about the function of the Crumbs proteins in mammalian neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…1B′,C′, red arrow), which confirms deletion from the cerebellum and validates the specificity of the Pals1 probe. In accordance with known neuroepithelium expression patterns (Ishiuchi et al, 2009;Kim et al, 2010), Pals1 proteins also localized to the apical surface in the URL and VZ of WT (Fig. 1D,F).…”
Section: Pals1 Is Expressed In Progenitors During Cerebellar Developmentsupporting
confidence: 84%
“…Polarity complexes include evolutionarily conserved apical complex proteins, such as the Crb complex (comprising Crbs, Pals1, Patj), the Par complex (Par3, Par6, aPKC) and basal complex proteins, such as the Scribble complex (Scribbles, Lgl, Dlg) (Assémat et al, 2008;Pieczynski and Margolis, 2011;Tepass, 2012). Previous studies have demonstrated that apical complex proteins are necessary for self-renewal of neural progenitor cells (Bultje et al, 2009;Costa et al, 2008;Kim et al, 2010), neuronal migration (Famulski et al, 2010;Solecki et al, 2006), axon determination (Chen et al, 2013;Shi et al, 2003), dendrite development (Tanabe et al, 2010), tissue polarity and neuron survival (Kim et al, 2010). However, there is little information about the function of apical complex proteins in the regulation of proliferation and differentiation of CGNPs, which lack typical apical-basal polarity.…”
Section: Introductionmentioning
confidence: 99%
“…First, apically localized cell junctions and the apicobasal polarity complexes have been implicated in the asymmetric cell division of NPCs (Farkas and Huttner, 2008). Mutations or experimental manipulations that affect the apical complex or the apical-basal polarity of NPCs often result in neurogenic abnormalities, such as precocious neuronal differentiation (Bultje et al, 2009;Cappello et al, 2006;Costa et al, 2008;Kim et al, 2010;Yokota et al, 2009). As the disruption of AJs may affect the apicobasal polarity of NPCs, the neurogenic phenotypes described here were potentially caused by this cell-autonomous mechanism.…”
Section: Roles Of the Cell-cell Junction In Neurogenesismentioning
confidence: 93%